Enhancing the solubility and dissolution rate of piperine via preparation of piperine-hydroxypropyl methylcellulose 2910 solid dispersion system using freeze-drying method - Lili Fitriani; Swari Tirtania; Salman Umar; Erizal Zaini (GarVal Editorial Ltda., 2024)
Context: Piperine is the main secondary metabolite isolated from the family Piperaceae. This biologically active ingredient has many pharmacological effects, though its low water solubility limits its absorption in gastrointestinal fluid. Aims: To improve piperine's solubility and dissolution rate by incorporating it into a solid dispersion system with the hydrophilic polymer hydroxypropyl methylcellulose (HPMC) 2910 via the freeze-drying method. Methods: Three different piperine:polymer ratios - 1:1, 1:2, and 2:1 (w/w) - were prepared. A physical mixture was also prepared in a 1:1 (w/w) ratio for comparison. The physicochemical properties of the samples were characterized by differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD) analysis, Fourier transform infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM). The solubility and dissolution tests were conducted in distilled water. Results: The solid dispersion characterization indicated a decrease in the melting points and endothermic peaks in the DSC analysis, a decrease in peak intensity in the PXRD patterns, no chemical interactions between active substances and polymers in the FTIR analysis, and significant morphological changes in the SEM analysis. The solubility test revealed the highest increase in piperine solubility (7.88-fold increase) for the 1:2 solid dispersion. Moreover, the 1:2 solid dispersion in the dissolution test led to the greatest amount of dissolved piperine (56.445 ± 1.13%). Conclusions: The piperine-HPMC solid dispersion system improved the solubility and dissolution rate of piperine.